Designing E-Voting to Increase the Efficiency and Transparency of the Election of the OSIS Chairman at SMP Negeri 7 Prabumulih - Cindy Feronica Wulandari; Andi Christian; Nur Aini Hutagalung (Yayasan Kita Menulis, 2026)
Cindy Feronica Wulandari (2021210014), Supervisor I Mr. Andi Christian S.kom., M.kom., and Supervisor II Ms. Nur Aini Hutagalung S.kom.M.,Si.,M.kom., entitled